Help with math question?

It's 2,6 and -6,-8,. I have to find x and y. I got 7/4 but it's marked as wrong can you tell me what I did wrong?

4 Answer(s)

You said you have to find x and y
what does that mean?
x = 2 and -6 in the two points you mentioned
y = 6 and -8 in the two points you mentioned
m = 7/4 is just the slope or the rate of change of y / rate of change of x
if this is a line, it represents an infinite number of x and y pairs
so you need to write down an infinite number of pairs to find all x and y values
you can an find equation , y = mx +b
you can find the y-intercept = b (set x = 0 and solve for y )
y = b
you can find the x -intercept (set y = 0 and solve for x )
0 = mx +b
mx =-b
x-intercept = -b /m
you want an equation of a line
y = mx +b
(7/4) is just m , it does not include b
(2,6) (-6, -8)
m = (-8 - (-6) ) / (-6 - 2) = -14/ -8 = 7/4
y = (7/4)x +b
(2,6)
6 =(7/4)*2 + b
b = 6 - (7/4)*2 = 6 - (7/4)*2 = (12 -7)/2 = 5/2
b = 5/2
=== equation of the line
y = (7/4)x + 5/2
=== x-intercept
x-intercept : 5/2
==== y-intercept
y-intercept: (-5/2/ (7/4) = -5/2 *(4/7) = -20/14 = -10/7
=== other points
plug values in the equation

y = (7/4)x + 5/2
x: -6 y: -8
x :0 y : 5/2
x :1 y: 17/4
x : 2 y : 6
x: 3 y : 31/4
x: 4 y : 38/4 = 19/2
and so on
You could find an infinite number of (x, y) pairs
=== equation for y
y = (7/4)x +5/2
solving for x
(7/4)x = y - 5/2
x = (4/7)y - (5/2)*(4/7) = (4/7)y - 10/7
==== equation for x
x = (4/7)y - 10/7

slope= (-8-6)/(-6-2)= -14/-8= 7/4

Here we have the line through (2,6) and (-6,-8) being given by (2--6)(y--8) = (6--8)(x--6) which can be manipulated and simplified to 7x - 4y = -10 in Standard Form, or to y = (7/4)x + 5/2 in Slope Intercept Form, or to x/(-10/7) + y/(5/2) = 1 in (Two) Intercept Form. Hence the x intercept is -10/7 and the y intercept is 5/2.

Graphs: https://www.desmos.com/calculator/03cpw5...

Question , as given , has no meaning.
Out of interest we have two points (2,6) and (-6,8)
gradient , m = 2 (-8) = - 1/4
Equation of line that passes thro` these points is :-
y - 6 = (-1/4) (x - 2)
y = (-1/4) x + 13/2